HD2C histone deacetylase and a SWI/SNF chromatin remodelling complex interact and both are involved in mediating the heat stress response in Arabidopsis. (4th August 2016) - Buszewicz, Daniel; Archacki, Rafał; Palusiński, Antoni; Kotliński, Maciej; Fogtman, Anna; Iwanicka‐Nowicka, Roksana; Sosnowska, Katarzyna; Kuciński, Jan; Pupel, Piotr; Olędzki, Jacek; Dadlez, Michał; Misicka, Aleksandra; et al.
Abstract: Studies in yeast and animals have revealed that histone deacetylases (HDACs) often act as components of multiprotein complexes, including chromatin remodelling complexes (CRCs). However, interactions between HDACs and CRCs in plants have yet to be demonstrated. Here, we present evidence for the interaction between Arabidopsis HD2C deacetylase and a BRM‐containing SWI/SNF CRC. Moreover, we reveal a novel function of HD2C as a regulator of the heat stress response. HD2C transcript levels were strongly induced in plants subjected to heat treatment, and the expression of selected heat‐responsive genes was up‐regulated in heat‐stressed hd2c mutant, suggesting that HD2C acts to down‐regulate heat‐activated genes. In keeping with the HDAC activity of HD2C, the altered expression of HD2C‐regulated genes coincided in most cases with increased histone acetylation at their loci. Microarray transcriptome analysis of hd2c and brm mutants identified a subset of commonly regulated heat‐responsive genes, and the effect of the brm hd2c double mutation on the expression of these genes was non‐additive. Moreover, heat‐treated 3‐week‐old hd2c, brm and brm hd2c mutants displayed similar rates of growth retardation. Taken together, our findings suggest that HD2C and BRM act in a common genetic pathway to regulate the Arabidopsis heat stress response. Abstract : Histone deacetylases (HDACs) and chromatin remodelling complexes (CRCs) regulate gene expression by modifying chromatin structure. Applying immunoprecipitation followed by protein mass spectrometry analysis, this study identifies HD2C HDAC as an interactor of BRM‐containing SWI/SNF CRC in Arabidopsis . Phenotypic and transcriptome analyses of 3‐week‐old hd2c, brm and brm hd2c plants indicate that HD2C and BRM ATPase jointly regulate heat stress response. Peptide pull‐down experiments indicate that HD2C binds to both histone H3 and histone H4 peptides. Several genes misexpressed in hd2c mutant show increased levels of H4K16 acetylation on gene bodies, suggesting that HD2C may cooperate in repressing heat‐responsive genes by removing lysine acetylation from nucleosomal histones.